Glial- and Neuronal-Specific Expression of CCL5 mRNA in the Rat Brain - Lanfranco, Maria Fe; Mocchetti, Italo; Burns, Mark P.; Villapol, Sonia (Frontiers in Neuroanatomy, 2018)
Chemokine ligand 5 (CCL5) belongs to a group of chemokines that play a role in the peripheral immune system, mostly as chemoattractant molecules, and mediate tactile allodynia. In the central nervous system, CCL5 and its receptors have multiple functions, including promoting neuroinflammation, insulin signaling, neuromodulator of synaptic activity and neuroprotection against a variety of neurotoxins. Evidence has also suggested that this chemokine may regulate opioid response. The multifunctional profile of CCL5 might correlate with its ability to bind different chemokine receptors, as well as with its unique cellular expression. In this work, we have used fluorescence in situ hybridization combined with immunohistochemistry to examine the expression profile of CCL5 mRNA in the adult rat brain and provide evidence of its cellular localization. We have observed that the highest expression of CCL5 mRNA occurs in all major fiber tracts, including the corpus callosum, anterior commissure, and cerebral peduncle. In these tracts, CCL5 mRNA was localized in oligodendrocytes, astrocytes, and microglia. Astrocytic and microglial expression was also evident in several brain areas including the cerebral cortex, caudate/putamen, hippocampus, and thalamus. Furthermore, using a specific neuronal marker, we observed CCL5 mRNA expression in discrete layers of the cortex and hippocampus. Interestingly, in the midbrain, CCL5 mRNA co-localized with tyrosine hydroxylase positive cells of the ventral tegmental area, suggesting that CCL5 might be expressed by a subset of dopaminergic neurons of the mesolimbic system. The expression of CCL5 mRNA and protein, together with its receptors, in selected brain cell populations proposes that this chemokine could be involved in neuronal/glial communication.